Efektivitas Komunikasi Telepon Seluler Penjualan Tomat Kecamatan Pangalengan Kabupaten Bandung - Kifli, Gontom (2015)
The access to information on the selling price of tomatoes by tomato growers is perceived very limited in the pastin Pangalengan District. The appearance of information technology, such as mobile phone, provides opportunities for tomatoes growers to obtain the access to more information, wider, faster and cheaper. The general objective of this research is to identify the behavior of tomato growers’ communication and the influence aspects of the use of mobile phones toward the effectiveness of communication in Pangalengan District. The method for this research is explanatory survey research. Two-steps random sampling has been used in this research with selected sample of 165 respondents. The research unit is focused on the tomatoes growers who used mobile phones. The result indicates that the tomato growers in Pangalengan District perceive the use of mobile phones provides benefits to have more options for the selling price of tomatoes. The result of statistical analysis shows that the use of mobile phones among tomato growers and tomato sellers has given significant effect on the effectiveness of communication and increasing the intensity of tomato sales.From this research, it is recommended to provide the information management of the selling price of tomatoes via mobile phones involving Agriculture Information Officer (PIP) which already exist today.